Pengaruh Penerapan Akuntansi Sektor Publik Terhadap Akuntabilitas Kinerja Instansi Pemerintah Dalam Mencegah Fraud - Santoso, Urip; Pambelum, Yohanes Joni (Jurnal Administrasi Bisnis, 2008)
Each of government units has responsibility to make report showing its accountabilityand trasparancy. To achieve this situation, the main problem is on the informationrelevancy and accurateness so the government can avoid frauds. Using entity theoryas the grand theory, agency theory as the middle theory and behaviour organizationsas supporting theory, the reseach show that both public sector accounting implementationand government financial report quality control will have an impact tothe accountability of government unit performance and then they also will make animpact to their effort to avoid fraud.Keywords: Public Sector, Performance Report, Financial Report, Fraud